Sex-dependent effects of food-restriction on cocaine self-administration and cocaine-seeking in rats - Mascarin, Alixandria T.; Mac, Ava M.; Kallakuri, Srinivasu; Greenwald, Mark K.; Perrine, Shane A. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionMisuse of drugs and natural rewards, such as food, share common neural pathways and comparably influence behavioral consequences. Food-restriction enhances drug-taking and drug-seeking behaviors in animals, but the effect of food-restriction on cocaine self-administration and cocaine-seeking in both sexes has not been well characterized.MethodsTherefore, the present study investigated differences between food-restricted vs. ad libitum-feeding male and female Wistar rats on the acquisition of cocaine self-administration and cue-induced reinstatement of cocaine-seeking.ResultsFood access sex-dependently altered the acquisition of cocaine self-administration such that food-restricted females, but not males, displayed an escalated intake behavior over time. Only food-restricted females differed significantly between active and inactive lever pressing during the reinstatement of cocaine-seeking session.DiscussionTaken together, these results suggest that food-restriction sex-dependently improves learning of cocaine self-administration that persists to alter cocaine-seeking behavior following abstinence.